Estudo dos anti-inflamatórios e analgésicos utilizados pelos idosos da Estratégia Saúde da Família de Porto Alegre - Ely, Luísa Scheer (2014)
Background: The high prevalence of anti-inflammatory and analgesic drug use by the elderly has been widely discussed in the literature because polymedication increases the risk of adverse effects and iatrogenic and drug interactions. Anti-inflammatory and analgesic drugs are primarily used to treat pain in the elderly, who are subject to high rates of arthrosis, arthritis and rheumatism. The prescription of anti-inflammatories and analgesics in the elderly should be individualized because the pharmacokinetics and pharmacodynamics of these drugs are altered in the elderly, which can cause numerous adverse effects. However, many studies have indicated a possible antioxidant action of anti-inflammatory drugs. Some studies have suggested that anti-inflammatory drugs induce the generation of reactive oxygen species, while other studies have demonstrated that they also have antioxidant activity. Aims: We report the findings of a transversal study of the use of anti-inflammatory and analgesic drugs among a random sample of elderly patients at the Family Health Strategy (FHS) in Porto Alegre, Rio Grande do Sul, Brazil. Methods: This study is part of the The multidimensional study of the elderly in the Family Health Strategy in Porto Alegre, Brazil (EMI-SUS) conducted over the period of March 2011 to December 2012. Data collection was performed by community health workers at the subjects homes using a general questionnaire and included sociodemographic data, life conditions and habits, chronic diseases and drug use. For this study, the focus was on drugs classified as anti-inflammatory or analgesic drugs according to the Anatomical Therapeutic Chemical classification system recommended by the World Health Organization. Blood was subsequently collected by the project team at the healthcare unit where the elderly patients were registered. The plasma levels of oxidative and inflammatory markers such as insulin, homeostatic model assessment-insulin resistance (HOMA-IR), malondialdehyde (MDA), ferric reducing ability of plasma (FRAP), advanced oxidation protein products (AOPP), interleukin-6 (IL-6) and ultra-sensitivity C-reactive protein (PCR_US) were determined. Anthropometric data were measured, but only body mass index (BMI) was used in this study. Results: Among the 758 elderly patients included in this study, between 60 and 111 years old, with the prevalence of anti-inflammatory and analgesic drug use was 28.8%. Paracetamol (67.9%) and ibuprofen (31.7%) were the most commonly used drugs. Women used antiinflammatory and analgesic drugs (P = 0.022) more frequently than men. Self-rated health was related to the use of anti-inflammatory and analgesic drugs, i.e., the worse the reported health, the greater the use of these drugs (P < 0.001). Of the conditions described by the elderly, hepatic disease (P = 0.004) and arthrosis/arthritis/rheumatism were associated with the use of anti-inflammatory and analgesic drugs. In addition, we observed that the higher the usage of medicines in general, the greater the use of anti-inflammatory and analgesic drugs (P < 0.001). Gastric problems reported by this elderly cohort may be associated with chronic or occasional use of NSAIDs (P = 0.042). There was no statistically significant association between the use of NSAIDs and oxidative or inflammatory markers. Conclusion: This study demonstrates the moderate use of anti-inflammatory and analgesic drugs by elderly patients at the FHS in Porto Alegre. Although these medications are important for the management of pain and inflammation, they may interfere with the improvement of the quality of life of the elderly. Thus, anti-inflammatory and analgesic drugs should be prescribed very carefully and individually in the elderly. With regard to inflammatory and oxidative markers, it is important to emphasize that the physiological effects of NSAIDs on markers of inflammation and oxidative metabolism are poorly characterized and controversial. This is the first study to demonstrate a lack of association between NSAID use and plasma levels of oxidative, antioxidant and inflammatory markers or the HOMA-IR value.